(untitled) (Student’s Journal of Health Research Africa, 2024)
Background Peripheral nerve sheath tumors (PNSTs) are rare, heterogeneous soft tissue neoplasms arising from Schwann cells, fibroblasts, and histiocytic or macrophage-like cells. They include benign tumors like schwannomas and neurofibromas and the highly aggressive malignant peripheral nerve sheath tumors (MPNSTs). Objective To evaluate the histopathological features and immunohistochemical (IHC) profiles of different PNSTs using S-100, SOX10, and CD56 markers. Methods This prospective observational study was conducted from June 2022 to July 2023 at a tertiary care teaching hospital in India. Thirty patients under 65 years with benign or malignant PNSTs were included. Histological features were assessed using light microscopy, and IHC staining was performed with S100, SOX10, and CD56. Data were analyzed using SPSS software, with a significance level set at p<0.05. Results Out of 30 cases, 17 (56.7%) were neurofibromas, 12 (40%) were schwannomas, and 1 (3.3%) was an MPNST. The mean age was 38.7 years, with a male-to-female ratio of 16:14. Tumor size varied significantly between types, with MPNST and schwannomas being larger than neurofibromas (P=0.07). Schwannomas frequently exhibited Antoni A and B patterns, Verocay bodies, and hyalinized blood vessels, while neurofibromas showed spindle cells and shredded carrot-type collagen. Immunohistochemistry revealed S100 positivity in 70% of tumors, SOX10 in 86.7%, and CD56 in 43.3%. Schwannomas showed higher S100 and CD56 expression compared to neurofibromas (p<0.05). Conclusions The study highlights distinct histological and immunohistochemical features of PNST subtypes, with significant differences in marker expression aiding in differential diagnosis. Larger-scale studies are needed to further validate these findings in diverse populations. Recommendations The study recommends using histopathological and immunohistochemical analysis with markers (S100, SOX10, CD56) for accurate PNST diagnosis and emphasizes the need for larger-scale, follow-up studies. It also highlights the importance of routine analysis, multidisciplinary collaboration, comprehensive patient care, and enhanced training for pathologists.